2020
DOI: 10.1039/d0ta00205d
|View full text |Cite
|
Sign up to set email alerts
|

A bimetallic-MOF catalyst for efficient CO2 photoreduction from simulated flue gas to value-added formate

Abstract: Bimetallic Ni/Mg-MOF-74 was reported as a catalyst for efficient CO2 photoreduction from simulated flue gas to generate value-added formate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 51 publications
0
44
1
Order By: Relevance
“…On the other hand, the CO 2 adsorption capacity for Fe 2 Mn-MOF was 42.0 cm 3 ·g –1 , which was substantially larger than those for Fe 3 -MOF (20.4 cm 3 ·g –1 ) and Fe 2 Ni-MOF (9.1 cm 3 ·g –1 ) (Figure B). These adsorption properties were lower than those previously reported NH 2 -UiO-66­(Zr) (68 cm 3 ·g –1 ) and Mg-MOF-74 (127 cm 3 ·g –1 ) . However, we also found a correlation between the CO 2 adsorption properties (25 °C, 1 atm) for Fe 2 M-MOFs and the photocatalytic activity (Figure C), suggesting that the enhancement of CO 2 adsorption capacity by Mn 2+ substitution in metal clusters contributed to the high activity of Fe 2 Mn-MOF.…”
Section: Resultscontrasting
confidence: 76%
“…On the other hand, the CO 2 adsorption capacity for Fe 2 Mn-MOF was 42.0 cm 3 ·g –1 , which was substantially larger than those for Fe 3 -MOF (20.4 cm 3 ·g –1 ) and Fe 2 Ni-MOF (9.1 cm 3 ·g –1 ) (Figure B). These adsorption properties were lower than those previously reported NH 2 -UiO-66­(Zr) (68 cm 3 ·g –1 ) and Mg-MOF-74 (127 cm 3 ·g –1 ) . However, we also found a correlation between the CO 2 adsorption properties (25 °C, 1 atm) for Fe 2 M-MOFs and the photocatalytic activity (Figure C), suggesting that the enhancement of CO 2 adsorption capacity by Mn 2+ substitution in metal clusters contributed to the high activity of Fe 2 Mn-MOF.…”
Section: Resultscontrasting
confidence: 76%
“…Because of the synergistic effect between Cu and Mg, the photostability of Mg x Cu 1– x -MOF-74 was enhanced considerably. 32 Furthermore, the stability of Mg-MOF-74 was highly affected by the M–O bond on the top of the metal–organic frame (M represents the metal species) and the metal center atoms (Mg). 31 The distortion and deformation of the coordination environment of Cu 2+ (i.e., Jahn–Teller effect) lead to the contraction of M–O bonds and improved photostability of Mg x Cu 1– x -MOF-74.…”
Section: Resultsmentioning
confidence: 99%
“… 25 27 Although bimetallic Mg-MOF-74 is widely used in thermocatalysis 28 , 29 and adsorption, 30 , 31 its use in CO 2 photocatalytic reduction is limited. 32 Guo et al prepared bimetallic NiMg-MOF-74 catalysts by using a solvothermal method and revealed that CO 2 can be photocatalytically reduced into formate over NiMg-MOF-74 under extremely harsh flue gas conditions. Furthermore, the excellent stability of NiMg-MOF-74 in the photocatalytic reaction was demonstrated through five cyclic photocatalytic experiments and X-ray diffraction (XRD) patterns after the photocatalytic reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the recent years, the progressively increasing CO 2 emission released by fossil fuel combustion brings out serious climate change and has threaten the human health, [1–3] so solving the environmental crisis becomes an extremely urgent global issue. It is generally acknowledged to be an efficient strategy for alleviating CO 2 pollution by photocatalytic reduction into value‐added chemicals such as CO, [4–7] CH 4 , [8–10] HCOOH [11–13] . Nevertheless, because of chemical inertness, it is hard to activate and convert CO 2 molecules, which thus requires reductive catalysts to help this reaction process [14–16] .…”
Section: Introductionmentioning
confidence: 99%